ANALISIS FAKTOR TERPAAN BERITA HOAX COVID-19 MASYARAKAT HINDU KOTA DENPASAR - Sintyananda Gayatri; I Gede Sutarya; I Gede Suwantana (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2022)
In the middle of the Covid-19 pandemic situation, people are not calm and sad, as a result of the many hoax news circulating on social media. WhatsApp is one of the three social media most often used by Indonesians, especially Hindus in Denpasar City in seeking for information. Low media literacy of digital media is one of the main cause of the rampant spread of hoaxes. Therefore, it is important to monitor the factors that influence the exposure of Covid-19 hoax news circulating in the Hindu community of Denpasar City. Based on the background, the formulation of the problem was obtained, namely: What factors influence the exposure of covid-19 hoax news in the Hindu community of Denpasar City?. This research uses a combination research approach, with a sequential explanatory model. This research was conducted in Denpasar City with the target of the Hindu community of Denpasar City. This study used a sample of 384 respondents and 10 informants. Quantitative data collection techniques in this study are in the form of questionnaires and qualitative data in the form of in-depth interviews. As for the findings of the research results, the factors that influence the exposure of covid-19 hoax news to the Hindu community of Denpasar City are factors of self-concept and basic understanding of hoaxes. The self-concept factor reveals a person's ability to distinguish hoaxes, the intensity of receiving hoax information, knowing the initial source of the spread of hoaxes, and how to respond to themselves when receiving hoaxes. The basic understanding factor of hoaxes reveals how people's understanding or basic knowledge of hoaxes.